High level of work stressors increase the risk of mental-emotional disturbances among airline pilots (Medical Journal of Indonesia, 2007)
Civilian airline pilots have one of the most stressful occupations. The aim of this study was to identify the effect of work stressors and other factors on mental-emotional disturbances among airline pilots. A cross-sectional study was done by interviewing selected pilots of an airline using appropriate questionnaires, during their routine medical examination from May to July 1999 in Jakarta. Five aspects of work stressor were assessed: working conditions, physical conditions of working environment, career development, organization and interpersonal relationship. Mental-emotional disturbances were determined by using the Symptom Checklist 90 (SCL 90) questionnaire. Data analysis was carried out using relative risk by Cox regression with constant time. From 128 subjects interviewed, 109 could be analyzed. Most of the subjects were married (73.4%) and college graduates (91.7%). The number of captains and first officers were almost equal. The prevalence of mental-emotional disturbances was 39.4%. Mental-emotional disturbances were significantly related to work stressors and moderately related to household tension (P = 0.184). Compared to pilots with low levels of work stressors, those with high or very high levels of work stressors had a risk of 4.6 times of mental-emotional disturbances [adjusted relative risk (RRa) = 4.64; 95% confidence interval (CI) = 1.01 - 19.65]. Adequate guides to cope work stressors and household tension which related to mental-emotional disturbance is recommended. (Med J Indones 2007; 16:117-21)